Memory Transmission: The Past as the Source of Determinism Image of Teluk Awur Society - Fadilah, Yuniardi; Pramudya, Akmal Dwi (2023)
The image of the people of Teluk Awur is attached to the impression of determinism. It is seen as due to the beliefs that exist among the people of Teluk Awur related to the story of the origin of the name Teluk Awur — which is believed to be history — itself. Thus, the research will attempt to look at the process of intergenerational memory transmission that has occurred among the people of Teluk Awur regarding the origin story of Teluk Awur so that it can continue to be accepted by the current generation of villagers. Thus, the research, as a qualitative research, will base the analysis process on the postmemory approach to see the memory transmission of the past story from the previous generation to the post-generation. This research found that the transmission process that occurs collectively is a form of affiliative transmission by bringing the story of the origin of Teluk Awur in the community. In addition, this story also forms a cultural memory for the people of Teluk Awur regarding Islam and the position of women